Rapid profiling of saponin extracts from Stichopus horrens sea cucumbers by mass spectrometry - Torreno, Vicenzo Paolo M.; Dumalan, Rafael Junnar P.; Batoctoy, Dessa Camille R.; Juinio-Meñez, Marie Antonotte; Yu, Eizadora T. (2021)
"Sea cucumbers produce bioactive compounds known as saponins. Structurally, these triterpene glycosides contain different sugar moieties that are attached to a lanostane-based aglycone backbone. This study aims to rapidly profile the saponins of the Philippine sea cucumber, Stichopus cf.horrens, y mass spectrometry (MS). MS and tandem MS (MS/MS) were acquired using a UPLC-QToF (ultra-performance liquid chromatography-quadrupole time-of-flight) mass spectrometer"-title page.
Includes bibliographical references.
Keywords: Mass spectrometry; Saponins; Sea cucumbers